2020
DOI: 10.1021/acsomega.0c04312
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance Degradation of Sandstone under Acidification

Abstract: In most oilfields, acid fracturing is widely used for oil production. Understanding the relationship between the individual factors (i.e., carbonate rock types, acid rock reaction kinetics, and deterioration of rock mechanical properties) can provide practical guidelines that can be used for the design and optimization of acid fracturing operation. This paper takes hydrochloric acid, acetic acid, and citric acid as the main research objects and carries out acidification experiments on sandstone in Changqing Oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Acidizing technology refers to the restoration or enhancement of the permeability of formation pores and cracks through the dissolving and erosioning action of acid on rock cement or blockages in formation pores and cracks, and so on. This technology shows obvious penetration‐enhancing effects in carbonate, sandstone, and shale reservoirs and is therefore widely used in oil, natural gas, and shale gas extraction applications 9–11 . In the field of coal, gas pressure and ground stress increase with the increase in mining depth, the permeability of coal rock decreases, and gas is difficult to desorbed from the reservoir, leading to a significantly higher threat of gas dynamic hazards.…”
Section: Introductorymentioning
confidence: 99%
“…Acidizing technology refers to the restoration or enhancement of the permeability of formation pores and cracks through the dissolving and erosioning action of acid on rock cement or blockages in formation pores and cracks, and so on. This technology shows obvious penetration‐enhancing effects in carbonate, sandstone, and shale reservoirs and is therefore widely used in oil, natural gas, and shale gas extraction applications 9–11 . In the field of coal, gas pressure and ground stress increase with the increase in mining depth, the permeability of coal rock decreases, and gas is difficult to desorbed from the reservoir, leading to a significantly higher threat of gas dynamic hazards.…”
Section: Introductorymentioning
confidence: 99%
“…In the past decades, physical permeability improvement measures, such as hydraulic fracturing, hydraulic punching, and hydraulic slitting, had been widely used in CBM mining, and they all played a positive role in increasing the permeability of seams and reducing impact ground pressure. However, in long-term practice, it is found that hydraulic permeability enhancement measures are difficult to form cross-link networks in rich-mineral seams with low permeability and cannot deal with the minerals filled in seams. , Acidification technology, which could improve the permeability of reservoirs through injecting acid solvent to dissolve minerals, has been widely used in the field of oil and shale gas to increase their production. Drawing on the application of acidification technology in other fields, some researchers did some acidification experiments in the field of CBM extraction and found that acidification technology could be used in seams to dissolve minerals, unblock the pore fracture, and convert the structure of coal, thereby changing its physical and chemical properties. Zha et al treated coal samples with different acid solvents and found that the content of minerals in coal reduced substantially and the permeability increased after acidification.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Acidification technology, which could improve the permeability of reservoirs through injecting acid solvent to dissolve minerals, has been widely used in the field of oil and shale gas to increase their production. 15 17 Drawing on the application of acidification technology in other fields, some researchers did some acidification experiments in the field of CBM extraction and found that acidification technology could be used in seams to dissolve minerals, unblock the pore fracture, and convert the structure of coal, thereby changing its physical and chemical properties. Zha et al 18 treated coal samples with different acid solvents and found that the content of minerals in coal reduced substantially and the permeability increased after acidification.…”
Section: Introductionmentioning
confidence: 99%
“…The rising effective stress inhibits the flow of coal seam gas and hinders gas extraction. To improve the effect of gas extraction in coal seams, pressure relief and permeability enhancement measures can be adopted on roof strata. , However, due to the geological evolution over time, pore fractures in reservoirs were blocked by minerals such as calcite, montmorillonite, and hematite. Physical permeability enhancement methods fail to alleviate this situation. Acidification, a multiphase chemical reaction occurring at the liquid–solid interface, can unblock pores and strengthen the development of the pore-fracture system of rock formation through chemical dissolution. Its process can be roughly divided into three phases: the movement of H + in the acid fluid system to the rock surface, the adsorption of H + on the rock surface and the chemical reaction, and the departure of the products from the rock surface at the reaction end (Figure ).…”
Section: Introductionmentioning
confidence: 99%